2018
DOI: 10.36911/pannmed.v12i2.24
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Penambahan Zirkonium Oksida Pada Bahan Basis Gigi Tiruan Resin Akrilik Polimerisasi Panas Terhadap Kekuatan Impak Dan Transversal

Abstract: Resin akrilik yang dipolimerisasi panas (RAPP) telah banyak digunakan sebagai bahan dasar gigi tiruan karena memiliki kelebihan seperti keadaan biokompatibel, jauh lebih estetis, mudah diproses, tidak memerlukan keahlian laboratorium untuk memperbaiki dan harganya relatif murah. Namun, RAPP adalah bahan dasar gigi tiruan yang mudah patah karena kekuatan impak dan transversal yang rendah. Kekuatan impak dan transversal dapat ditingkatkan dengan penambahan bahan penguat nanopartikel zirkonium oksida (ZrO2). Pene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 5 publications
1
7
0
1
Order By: Relevance
“…Previous study reported that 5% ZrO 2 nanoparticles were biocompatible materials in increasing compatibility with polymers to enhance the impact and transverse the strength of the denture. 9 The porosity of the acrylic resin denture base with ZrO 2 nanoparticle filler demonstrated significant differences between groups. The control group, acrylic resin with ZrO 2 in a concentration of 2.5% and 5% and had a significant value.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Previous study reported that 5% ZrO 2 nanoparticles were biocompatible materials in increasing compatibility with polymers to enhance the impact and transverse the strength of the denture. 9 The porosity of the acrylic resin denture base with ZrO 2 nanoparticle filler demonstrated significant differences between groups. The control group, acrylic resin with ZrO 2 in a concentration of 2.5% and 5% and had a significant value.…”
Section: Discussionmentioning
confidence: 93%
“…It is a Zirconium dioxide (ZrO 2 ) nanoparticle material characterized by great strength and hardness, non-abrasiveness, non-toxicity, biocompatibility, and low thermal conductivity. 9 ZrO 2 nanoparticles has been validated through in vitro and in-vivo research and thus its application is recommended in dental and other biomedical treatments. ZrO 2 nanoparticles are also recommended for coating materials on PMMA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed various transverse power values in the same group, and the varying results can be caused by several factors that affect the sampling process. 11 The presence of residual monomer content that acts as a plasticizer would weaken the polymer bond chain allowing deformation to occur more easily and altering the strength values. The second factor is due to the manual stirring technique and the possibility of air trapping in the heat polymerized acrylic resin matrix and internal porosity, which is not visible on the sample surface.…”
Section: Discussionmentioning
confidence: 99%
“…This linkage increases intermolecular adhesion and compatibility between inorganic CaCO3 and the polymer matrix. 9,10,11…”
Section: Introductionmentioning
confidence: 99%